Pedagogic Translanguaging in EFL Classroom: A Study at MTsN 1 Mataram - Safitri, Bq. Diana; Arafiq; Udin; Yusra, Kamaludin (Program Studi Pendidikan Bahasa Inggris, 2024)
Translanguaging is the practice of changing the usage of two different languages or more in order to improve communication and enrich the linguistic aspects of language use. This study presents the use of translanguaging in EFL classroom by English teachers. The main aim of this study is to describe the components and the functions of translanguaging used by the English teachers at MTsN 1 Mataram during teaching and learning process. The subject of this study consisted of two English teachers who teach at MTsN 1 Mataram. The results of this study show that there are two components and six functions of translanguaging used by the English teachers. The translanguaging’s components used by the English teachers were dominated by 58% code-switching, and 42% translating and interpreting. The difference between translanguaging and code switching is in the concept. Translanguaging allows anyone to use more than two languages without constraints, yet code-switching has its own limitations. In addition, the highest frequency of translanguaging functions is message qualification which occurred 30 times or 31%. Meanwhile, the lowest frequencies are quotations, and personalization vs objectification, where each of these functions contains one data. The implications of translanguaging in education are vast and can have a positive impact on various aspects of teaching and learning